Ultrasonic instrumentation for accurate real time corrosion monitoring using permanently installed transducers - Suchato, Nutthawut (2019)
Corrosion assessment helps to ensure that a ship can be safe to use without catastrophic failure. Periodic human-conducted ultrasonic inspection is commonly used for the assessment of structural integrity of ships using time-of-flight (ToF) measurements. Unfortunately, the accuracy of the ultrasonic thickness estimate is reduced when the measurement is confronted by rough surfaces. In addition, such inspections require a lot of time and cost a lot of money to perform. However, continuous in service structural health monitoring of the hull could potentially translate into a reduction of maintenance costs by extending time intervals between costly dry dock periodic inspection and/or their durations.